Writing in the biological sciences a comprehensive resource for scientific communication - Hofmann, Angelika H. 1965- (Oxford University Press, 2025)
""Writing in the Biological Sciences: A Comprehensive Resource for Scientific Communication" serves as a comprehensive "one-stop" reference guide to scientific writing and communication for budding professionals in the life sciences and related fields. The book is designed to function both as a free-standing textbook for a course on writing in the sciences and as an accompanying text or reference guide in courses with writing-intensive components. It covers all the basics of scientific communication that students need to know and master for successful scientific careers. The book lays the foundation for professional writing by starting with basic scientific writing principles and then by applying these principles to lab reports, summaries, and critiques and eventually also to full-fledged scientific research articles, review articles, and grant proposals. Practical advice for organizing academic presentations and posters as well as for putting together job applications is also included"--
Keywords: Communication in science; Scientific literature; Technical writing; Information scientifique; Sciences / Documentation; Rédaction technique; technical writing; Wissenschaftliches Manuskript; Methode